Case Report: Severe Colonic Crohn Disease Initiated after Liver Transplantation Requiring Surgery - Sapienza, Gabriela Feres; Pinto, Rodrigo Ambar; Simões, Italo Beltrão; Traldi, Maria Clara; Marques, Carlos Frederico; D'Albuquerque, Luiz Augusto Carneiro; Rocha, Manuel; Nahas, Sergio Carlos; Marchiolli, Camila; Ledesma, Felipe Lourenço (Journal of Coloproctology, 2024)
Introduction A patient using tacrolimus for hepatocyte transplantation (HT) was diagnosed with Crohn disease (CD) with mainly colonic involvement, despite drug immunosuppression due to the previous transplant. Upon routine colonoscopy, a lateral growth lesion was detected, which was endoscopically unresectable. Therefore, it was decided to perform a total colectomy with burial of the rectum and terminal ileostomy. During surgery, thickening of the terminal ileum and cecum was visualized, along with “fat-wrapping” and thickening of the entire mesocolon.Discussion Immunosuppression in patients with HT should control the activity of autoimmune diseases. However, the literature shows evidence of some reports of inflammatory bowel disease (IBD) activity after liver transplantation (LT). A review article from 2015 highlighted 92 cases of IBD after LT in the literature, with only 14 being CD, demonstrating that this is a rare phenomenon. Among the hypotheses, cytomegalovirus infection is related to the increased disease activity in patients with IBD and HT. In addition, several studies show an association between the drugs used in immunosuppression after LT and relapsed IBD, important data in patients receiving tacrolimus.Conclusion The occurrence of CD after LT is rare and seems to have a direct association with the immunosuppression used to prevent rejection of the transplanted organ.
Keywords: inflammatory bowel disease; Crohn Disease; liver transplantation; total colectomy; treatment surgical